High-sensitivity point-of-care measurement of cardiac troponin - Cullen, Louise; Mair, Johannes; Hammarsten, Ola; Stengaard, Carsten; Boeddinghaus, Jasper; Daniels, Lori B.; Huber, Kurt; Giannitsis, Evangelos; Jaffe, Allan S.; Kimenai, Dorien M.; Krychtiuk, Konstantin A.; Lindahl, Bertil; et al. (European heart journal, 2025)
New technologies enabling access to high-sensitivity cardiac troponin (hs-cTn) assays at the point of care (POC) are available for routine use. POC technology can accelerate cardiac troponin testing within the hospital setting and support testing in other healthcare environments. Pre-analytical and analytical issues unique to POC testing are discussed. The opportunities and the evidence needed to support the routine use of hs-cTn POC assays in clinical care are outlined. Based on recent developments, the potential impact of hs-cTn at the POC in multiple clinical settings is described, and a roadmap of the steps required for successful implementation is provided.